2019
DOI: 10.1111/jade.12230
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Feedback: An Application Framework for Group Feedback Videos in Design

Abstract: This article presents the development and application of group feedback videos (GFVs) in design education. A case study shows how visually‐rich GFVs were developed in a practice‐based design studio subject where learners were required to work in teams and independently calibrate an ability to form judgements on the qualities of their own work. Breaking away from traditional models of individual written feedback, students were instead provided with holistic reviews of project outcomes in a GFV format. Assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…However, this finding was different from some earlier studies in the 1970s, which argued that the FtF format had the highest communication richness [20][21][22][23]. While the research findings revealed no significant difference between the CMC and FtF communication formats in the perception of the availability of immediate feedback, previous studies did argue that the CMC media richness for interactivity was still behind the FtF format [11,35].…”
Section: Discussioncontrasting
confidence: 92%
“…However, this finding was different from some earlier studies in the 1970s, which argued that the FtF format had the highest communication richness [20][21][22][23]. While the research findings revealed no significant difference between the CMC and FtF communication formats in the perception of the availability of immediate feedback, previous studies did argue that the CMC media richness for interactivity was still behind the FtF format [11,35].…”
Section: Discussioncontrasting
confidence: 92%
“…In the Design course, the GFV application facilitated the collaborative work and developed the skills of the students (Brown & Fridman, 2020). Even this application favored the critical thinking and realization of the discussion forums during the face-to-face sessions (Brown & Fridman, 2020). Technological advances are causing substantial changes in the Faculty of Arts and Design (Costantino, 2018).…”
Section: Use Of Technology In the Faculties Of Arts And Designmentioning
confidence: 99%
“…Technology is transforming the school activities, functions and attitudes of students and teachers at the Faculties of Arts and Design (Marshalsey & Sclater, 2019;Strycker, 2020). Consequently, institutions have the opportunity to build new educational spaces with the support of digital tools (Brown & Fridman, 2020;Kerr & Lawson, 2020;Salas-Rueda, Salas-Rueda, & Salas-Rueda, 2020).…”
Section: Use Of Technology In the Faculties Of Arts And Designmentioning
confidence: 99%
See 2 more Smart Citations